2020
DOI: 10.3329/medtoday.v32i1.44812
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Patterns of Retinal Eye Diseases in Outpatient Department of a District Hospital in Bangladesh

Abstract: Introduction: Retinal diseases especially those due to diabetes and AMD are coming up as important causes of blindness and visual impairment. Our study is to evaluate the frequency and pattern of retinal diseases in ophthalmic outpatient department of a district hospital in Bangladesh. Materials and Methods: A total number of 173 referred new retina cases were reviewed at outpatient department of the 250 beded General Hospital, Jamalpur, Bangladesh, between February 2017 and November 2017. Data was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
1
2
1
Order By: Relevance
“…In this study, cataract, glaucoma, retinal detachment, corneal opacities, maculopathy, chemical injury, trauma, and uveitis were more commonly reported among male patients (see Table 4). These conditions are potential causes of VI and permanent loss of sight (10,(21)(22)(23)(24). Our findings rationalize with that of another study that indicated that ocular trauma is more common among males (25).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, cataract, glaucoma, retinal detachment, corneal opacities, maculopathy, chemical injury, trauma, and uveitis were more commonly reported among male patients (see Table 4). These conditions are potential causes of VI and permanent loss of sight (10,(21)(22)(23)(24). Our findings rationalize with that of another study that indicated that ocular trauma is more common among males (25).…”
Section: Discussionsupporting
confidence: 91%
“…is prevalence is higher than the prevalence reported in other hospital-based studies in developing countries [44][45][46]. However, the prevalence of retinal diseases (1.6%) was lower than the prevalence in other developing countries [4,6,12,13].…”
Section: Discussioncontrasting
confidence: 53%
“…Retinal diseases are the leading cause of irreversible blindness in developed countries and their prevalence is gradually increasing in the developing world [4]. Diseases of the retina such as diabetic retinopathy (DR), hypertensive retinopathy, retinal tear and detachment, epiretinal membrane, macular hole, age-related macular degeneration (AMD), vascular occlusions, and retinitis pigmentosa are significant causes of visual impairment and blindness [5,6]. For instance, diabetic retinopathy is known to be the main cause of blindness among the working population in the developed world [7,8] and AMD is the leading cause of blindness among the older population [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation